Oral glucocorticoid use and osteonecrosis in children and adults with chronic inflammatory diseases: a population-based cohort study. Issue 7 (21st July 2017) - Horton, Daniel B; Haynes, Kevin; Denburg, Michelle R; Thacker, Mihir M; Rose, Carlos D; Putt, Mary E; Leonard, Mary B; Strom, Brian L
Abstract : Objectives: We studied oral glucocorticoids and osteonecrosis, a rare but serious bone disease, in individuals with various chronic inflammatory diseases. We hypothesised that we would find stronger associations in adults versus children and in people with autoimmune diseases. Design: Retrospective cohort study. Setting: Population-representative data (1994–2013) from general practices in the UK. Participants: Children and adults diagnosed with asthma; inflammatory bowel disease; juvenile, psoriatic or rheumatoid arthritis; psoriasis; or systemic lupus. Exposures: Oral glucocorticoid patterns. Primary and secondary outcome measures: Diagnosed osteonecrosis (primary) and osteonecrosis plus clinical features (eg, symptoms, pain medication, surgical repair) (secondary). Discrete time failure models estimated the adjusted hazard ratio (aHR) of incident osteonecrosis following oral glucocorticoid exposure. Hypothesis testing was one sided (with corresponding 90% CI) since glucocorticoids were unlikely protective. Results: After adjusting for demographic, disease-related and health utilisation factors, glucocorticoid exposure was associated with osteonecrosis in adults (ages 18–49, aHR 2.1 (90% CI 1.5 to 2.9); ages ≥50, aHR 1.3 (90% CI 1.01 to 1.7)). However, low-dose glucocorticoids, corresponding to average doses <7.5 mg prednisolone daily and maximum doses <30 mg daily, were not associated with osteonecrosis in adults. Furthermore, even at high glucocorticoid doses, there was no evidence of increased osteonecrosis among glucocorticoid-exposed children (p=0.04 for interaction by age) (any glucocorticoid exposure, ages 2–9: aHR 1.1 (90% CI 0.7 to 1.7); ages 10–17: aHR 0.6 (90% CI 0.3 to 1.6)). Arthritis, inflammatory bowel disease and lupus were independently associated with osteonecrosis, but there was a similar dose relationship between glucocorticoids and osteonecrosis among adults with low-risk and high-risk diseases. Conclusions: Glucocorticoid use was clearly associated with osteonecrosis in a dose-related fashion in adults, especially young adults, but this risk was not detectable in children. The absolute risk of glucocorticoid-associated osteonecrosis in the general paediatric population and in adults taking low glucocorticoid doses is at most extremely small.